Pola Pengembangan Kompetensi Kepemimpinan Bagi Aparatur Pemerintah dalam Menghadapi Tantangan Global (Studi Kasus Pada Penyelenggaraan Diklat Kepemimpinan Tingkat IV Di KESDM) - Makmun Abdullah (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2018)
Leadership development program is an integrated leadership quality development program towards individuals and organizations to achieve organizational goals.Â  This is important in response to the urgent need to prepare competent leaders in the face of global challenges and uncertainty conditions. Through appropriate leadership development programs, government/institutions are expected to achieve their goals effectively and efficiently. Currently there has been a paradigm shift in leadership development programs that more targeted to the human side by focusing on individuals rather than on their own management processes. This research is expected to answer questions related to the benefits, effectiveness, and development of Leadership Training program organized by the Ministry of Energy and Mineral Resources at this time. The approach of this research is literature review and qualitative descriptive by distributing questionnaires with respondents of alumni of Diklatpim Level IV at KESDM Year 2017. The results show that the Leadership Training which has been held essentially in accordance with the trend of leadership development that is considered most effective model at this time. The alumni of leadership training program have also benefited from the implementation of the training.